Systematic Review of the Determinants of Technology Transfer in the Security and Defense Sector - Aguirre Rivera , Marco Antonio; Huayan Monzon, Franklin Edison (Athenea Engineering sciences journal, 2025)
Technology transfer in the field of security and defense is a complex phenomenon shaped by institutional dynamics, organizational capabilities, and public policy instruments. This study aimed to synthesize the main determinants that explain technology transfer processes in this sector through a systematic literature review. A corpus of relevant studies was selected following defined inclusion criteria, and qualitative quality assessment methods were applied. The findings revealed four convergent axes: policy orientation toward impact rather than volume, strengthening of governance structures with clear functions and resources, efficient process management supported by consistent operational metrics, and the establishment of collaborative relationships based on trust. The study confirmed that the success of technology transfer depends on the articulation among incentives, institutional frameworks, and technical capacities, highlighting the need for standardized metrics and more robust analytical approaches.